Vehicle Components Defect Detection via Machine Vision - Petrosyan, Armen S. (Изд-во НАН РА)
The task of quality control and automatic defect detection on production lines is one of the most important tasks of machine vision and digital image processing (DIP). This article provides one example of solving such a problem using various DIP algorithms. Որակի ստուգման նպատակով արտադրական հոսքագծերի ավտոմատացման խնդիրը հանդիսանում է թվային պատկերների մշակման արդիական խնդիրներից մեկը: Աշխատանքում նկարագրված է այդ խնդրի լուծման մի օրինակ մեքենայական տեսողության միջոցներով: Задача проверки качества и автоматизации нахождения дефектов изделий на производственной линии является одной из актуальных задач в цифровой обработке изображений. В работе описан один пример для решения такой задачи средствами машинного зрения.
Keywords: Mathematical cybernetics; Computer science